Car rental system with e-commerce technology using Zend framework - Mohd Norlihazmey, Ghazali (2013)
Currently, car rental is famous among the UMP's students in order to rent a car, they need to find it via social network and get the phone number of the car's owner through it. To give the advantages for both owner and customer, the car rental system was developed...